Stiffness properties of modified asphalt using high density polyethylene (HDPE) as aggregate additive material contain portland cement and fly ash as a filler - Noridayu, Zainal (2014)
Nowadays, plastic are being produced in a large amount because it has become one of the necessity for users to carry good and food containers. There is a various types of plastic that are produced such as High Density Polyethylene (HDPE), Polyethylene (PET), Low Density Polyethylene (LDPE) etc. The main objective of this study is to evaluate the stiffness characteristic of the modified asphalt mixture using HDPE as additive material and Portland cement and Fly ash as mineral filler by using the Indirect Tensile Stiffness Modulus (ITSM). The modified asphalt mixtures were produced from the content of HDPE pallet form. The size of recycled HDPE pallet is passing at sieve size between 3.35mm and 2.36mm. The HDPE was added into the mixture with a difference percentage which is 2%, 4%, 6%, 8 1/o and 10%. The temperature that was used to evaluated the stiffness characteristic of the control asphalt and modified asphalt is 20°C. The weight of the bitumen content that was used is, 5% as follow hot mix asphalt 14 (ACB 14) in Public Work Department (PWD) requirement. The result shows that the stiffness modulus value was increased when the content of HDPE is increased. The additional of HDPE in asphalt mixture with Portland Cement as a filler was enhanced the stiffness of the modified asphalt. The modified asphalt that was using Portland cement as mineral filler shows the positive effects on stiffness modulus until the maximum of HDPE percentage at 10%. Meanwhile, the trend of line asphalt mixture using fly ash as a filler was shows that it is decreased with the additional of HDPE amount in asphalt mixture. The result shows that the stiffness was decreased with the additional of HDPE and at certain percentage of HDPE which is at 8% and 10%, the stiffness are more less than control asphalt. The optimum stiffness modulus of modified asphalt contained Portland cement as mineral filler is at 10% HDPE content while the fly ash is 2% of HDPE content. In conclusion, the additional of recycled HDPE in modified asphalt give a positive effect to stiffness characteristic .of the modified asphalt. The control and modified asphalt that was used in this research also comply with the PWD requirement. The results also shows that the data was fluctuate from 0% to 10% HDPE content. The results indicates that the additional of recycled HDPE in asphalt mixture was improved the stiffness modulus performance compared with the control asphalt mixture.